“Sexual” behavior in parthenogenetic lizards (Cnemidophorus) - Crews, David (1980)
All-female, parthenogenetic species afford a unique test of hypotheses regarding the nature and evolution of sexuality. Basic data on the behavior of parthenogens are lacking, however. We have discovered, from observations of captive Cnemidophorus uniparens, C. velox, and C. tesselatus, behavior patterns remarkably similar to the courtship and copulatory behavior of closely related sexual species. Briefly, in separately housed pairs, one lizard was repeatedly seen to mount and ride its cagemate and appose the cloacal regions. Dissection or palpation revealed that, in each instance, the courted animal was reproductively active, having ovaries containing large, preovulatory follicles, while the courting animal was either reproductively inactive or postovulatory, having ovaries containing only small, undeveloped follicles. These observations are significant for the questions they raise. For example, is this behavior a nonfunctional vestige of the species' ancestry, or is this behavior necessary for successful reproduction in the species (e.g., by priming reproductive neuroendocrine mechanisms as has been demonstrated in sexual species)?